Pendampingan Berbasis Participatory Action Research pada UMKM Jiddah Krenyes Jakarta: Transformasi Pemasaran Melalui Penetrasi Retail Modern Bright Store Pertamina untuk Meningkatkan Daya Saing - Jimmy Wijaya; Narotama Aulia Fazri; Surya Suganda; Sudarmiatin Sudarmiatin; Yuli Soesetio (FKIP, Universitas Palangka Raya, 2026)
MSMEs in the snack food sector face dual pressures: competition with large-scale national brands on one side, and the requirement to meet modern retail standards on the other. This Community Service activity was conducted at Jiddah Krenyes, a home-industry potato chips MSME in Jakarta affiliated with the Jakarta Entrepreneur community, using a Participatory Action Research approach with four cycles: plan, act, observe, and reflect. The intervention focused on marketing transformation toward modern retail penetration through Bright Store Pertamina via six sequential phases: audit and planning, visual identity and branding optimization, digital content strategy development, Bright Store penetration through fulfillment of seven retail requirements, integrated promotion activation, and monitoring and evaluation. Reflective evaluation confirms substantive changes in the partner's business capacity: gradual fulfillment of modern retail legality requirements, consistent brand identity strengthening, more structured digital content strategy, establishment of a Bright Store pilot outlet partnership, and more effective omnichannel integration. This activity contributes to the validation of PAR integration with modern trade marketing and omnichannel strategy frameworks for Indonesian snack food MSMEs.